2020
DOI: 10.31002/metathesis.v4i2.2360
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Students’ Attitudes towards EFL Learning in Response to Industry 5.0

Abstract: The main objective of this study was to identify the attitudes of Indonesian students towards studying English vis-a-vis their readiness to compete in the fifth industrial revolution era. The data obtained from a four-point scale questionnaire administered to 216 participants from 12 universities across Indonesia were analyzed through a descriptive case study procedure. The findings showed that even though most students had positive attitudes towards EFL learning ( = 3.29) as well as towards Industry 5.0 ( = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Communication skills using English are needed for students' future careers. This is in line with the results of previous research that showed that students are not ready for the era of society 5.0 in terms of English proficiency due to the absence of intrinsic motivation to learn the language, student awareness of the needs of English competence is not in line with the desire to meet these needs [21], [22].…”
Section: B Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Communication skills using English are needed for students' future careers. This is in line with the results of previous research that showed that students are not ready for the era of society 5.0 in terms of English proficiency due to the absence of intrinsic motivation to learn the language, student awareness of the needs of English competence is not in line with the desire to meet these needs [21], [22].…”
Section: B Discussionsupporting
confidence: 90%
“…Not only adjusting the curriculum and training educators but teaching soft skills that play a role in the era of society 5.0 is also a must. Although machines can perform many repetitive tasks better than humans, humans are more skilled in creative activity, creativity, critical thinking, social interaction, and physical abilities [21]. Therefore, Teacher Training Institution must develop student competencies so that its graduates can work with machines effectively and efficiently side by side rather than competing with them.…”
Section: B Discussionmentioning
confidence: 99%
“…In her view, a higher level of exposure to the language, and a more comprehensive approach to second language teaching contributes to students having a positive impression of the subject. While research on non-pesantren secondary schools suggests that most students in Indonesia have positive learner attitudes toward English (Afdian & Wahyuni, 2020; Kharismawan, 2018;Yosintha, 2020), Bu Wati's comments above indicates that the opposite may be the case among pesantren students. This is despite the recognition pesantren teachers give to the broader value of English as an important language to learn in an era of advanced hyper-globalization.…”
Section: Episode 1: the Pragmatic Challenges Of Elt In Pesantren Schoolsmentioning
confidence: 99%
“…Improving services from the various features provided can increase the activity of an organization (Kuzieva, 2019) Shukshina et al, 2020) is a part of information technology (Sofyani et al, 2020). Universities are currently trying to improve the quality of their information to students to meet the demands of the 5.0 industrial revolution (Yosintha, 2020). The focus of this information technology is to provide information systems in various aspects of activities in the industrial world, in which developments continue to rise rapidly (Oztemel & Gursev, 2020;Dwivedi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%